Chemical Characterization of Cow Manure and Poultry Manure after Composting with Privet and Cypress Residues. Issue 22 (16th December 2018) - Haroon, B.; Abbasi, A. M.; Faridullah; An, P.; Pervez, A.; Irshad, M.
ABSTRACT: Investigating available nutrients and non-essential elements in manures is important for safe management of animal and plant waste. Therefore, this study was carried out to chemically characterize cow manure (CM) and poultry manure (PM) after co-composting with privet and cypress residues. Results showed that heavy metals concentrations in manures varied as Fe > Zn > Mn > Cu > Ni > Pb > Cd. Addition of privet and cypress residues to both manures altered the extractability of heavy metals after composting. Higher concentrations of heavy metals were observed in manures at 1:0 ratio while lowest was noted in both CM and PM composted with plant residues at 1:2 ratio. Total K, Ca, and Mg significantly increased when CM and PM were co-composted with privet and cypress residues. There was an increase in the P content in co-composted CM with privet residual application whereas a reduction in total P was noticed with the addition of cypress plant residues in both manures. Manures amended with plant waste reduced N content. Both CM and PM retained higher NO3 content without plant residues.